2012
DOI: 10.1589/jpts.24.633
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Balance under Dual and Simple Task Conditions in Children with Attention Deficit Hyperactivity Disorder

Abstract: Abstract.[Purpose] The purpose of this study was to make a comparison of dynamic balance ability between dual and simple task conditions. [Subjects and Methods] Nine children with attention deficit hyperactivity disorder (9.00 ± 2.12 years) and 10 healthy children (9.67 ± 2.75 years) were recruited. Each group was asked to do an obstacle crossing alone and the obstacle crossing combined with a stimulus response task. The Qualisys motion capture system was used to capture full-body motion. The parameters measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Vilensky et al 9 ) reported results similar to ours, as the stance time was statistically longer for the autistic group than for the control group. However, Calhoun et al 2 ) reported opposite results to those of our study, as they reported that cadence was higher for the autistic group than for the control group aged between 5 and 9 years (mean age, 6.3 years; mean height, 121.0 cm; mean weight, 29.3 kg).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Vilensky et al 9 ) reported results similar to ours, as the stance time was statistically longer for the autistic group than for the control group. However, Calhoun et al 2 ) reported opposite results to those of our study, as they reported that cadence was higher for the autistic group than for the control group aged between 5 and 9 years (mean age, 6.3 years; mean height, 121.0 cm; mean weight, 29.3 kg).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies demonstrated various locomotor skills and gait problems associated autism due to a lack of postural control, stability, and balance, as well as due to coordination impairments 7 , 8 , 9 , 10 , 11 ) . Calhoun and associates 2 ) reported that hypotonia, muscle rigidity, akinesia, bradykinesia, and postural control impairments can lead to unstable and abnormal movements during daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…This means that recruitment of these structures can compensate for inefficient BG 28 , 29 ) . Chen et al 30 ) compared the between effects of simple versus dual-task training on dynamic balance but in children with attention deficit hyperactivity disorder as they found it effective in favour to dual-task training. Future studies should investigate the effect of various cognitive skills on balance through postural sway 31 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been observed that children with autism exhibit problematic behaviors such as irritability, lethargy, stereotypy, and hyperactivity 8 ) . Sensory and motor problems often present additional challenges to children with developmental problems 9 ) .…”
Section: Introductionmentioning
confidence: 99%